A yttria dispersion strengthened copper-chromium-niobium alloy and a method for producing the same
Patent Information
- Application Number
- CN202611021028.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]为解决铜合金粉末3D打印适配性差、氧化物分布不均、析出相易聚集长大、3D打印件缺陷多及高温性能不足等技术问题,本发明提供一种氧化钇弥散强化铜铬铌合金及其制备方法
本发明的氧化钇弥散强化铜铬铌合金及其制备方法,所述铜铬铌合金具体含量百分比如下:Cr含量为3.5~4.5%,Nb含量为1.8~2.2%,Y2O3含量为0.05~0.5%,O含量(除Y2O3结合氧外)≤0.04%,Fe含量≤0.05%,余量为Cu。具体制备步骤如下:(1)球磨混料;(2)对混合后的粉末进行等离子球化并干燥过筛;(3)对复合粉末进行激光选区熔化成形;(4)对所得合金块进行去应力退火;(5)对退火后的合金块进行热等静压处理;(6)对热等静压后的合金块进行时效处理。本发明对铜铬铌合金的进行成分设计,通过降低Cr、Nb元素含量并引入Y2O3,以细化微观组织,且通过三级热处理消除合金缺陷、促进沉淀相析出,使得本发明制备的铜铬铌合金在保证高导电导热性的同时,兼具沉淀、弥散协同强化机制,提高了合金的高温力学性能。
Smart Images

Figure CN122979696A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of materials preparation technology for extreme heat applications in spacecraft, and particularly to a yttrium oxide dispersion-strengthened copper-chromium-niobium alloy and its preparation method. Background Technology
[0002] With the rapid development of aerospace technology, new-generation liquid rocket engines are constantly evolving towards higher thrust-to-weight ratios and higher combustion chamber pressures, placing extremely stringent requirements on the high-temperature resistance, thermal conductivity, and low-cycle fatigue life of combustion chamber and nozzle lining materials. While traditional precipitation-strengthened copper alloys such as Cu-Cr, Cu-Zr, and Cu-Cr-Zr possess excellent room-temperature thermal conductivity, their nanoscale precipitated strengthening phases are prone to coarsening and remelting at temperatures above 450°C, leading to a sharp decline in high-temperature strength and failing to meet the requirements for long-term stable operation of high-performance engines. Simultaneously, to further improve cooling efficiency, the cooling channel structures of engine linings and nozzles are becoming increasingly sophisticated and complex. Traditional smelting and sintering processes struggle to achieve high-precision forming of complex thin-walled structures, hindering further improvements in engine performance.
[0003] Current research on high-performance copper alloys is largely focused on powder metallurgy, with limited research combining it with selective laser melting (SLM) technology. The core bottleneck lies in the fact that composite powders prepared by traditional mechanical alloying are often irregular flakes with poor flowability and spreadability, failing to meet the powder requirements of SLM processes. Although some studies have attempted to improve powder morphology using plasma spheroidization technology, the oxide distribution during spheroidization is difficult to precisely control, the Cr2Nb phase easily aggregates and grows, and a systematic solution for matching and optimizing subsequent printing and heat treatment parameters has not yet been developed, making it difficult to fabricate fully dense, high-performance complex structural components. Summary of the Invention
[0004] To address the technical problems of poor compatibility of copper alloy powder in 3D printing, uneven oxide distribution, easy aggregation and growth of precipitates, numerous defects in 3D printed parts, and insufficient high-temperature performance, this invention provides a yttrium oxide dispersion-strengthened copper-chromium-niobium alloy and its preparation method.
[0005] The technical solution adopted by this invention to solve its technical problem is: In a first aspect, the present invention provides a yttrium oxide dispersion-strengthened copper-chromium-niobium alloy powder, which is composed of the following mass percentage components: Cr 3.5%~4.5%, Nb 1.8%~2.2%, Y2O3 0.05%~0.5%, with the balance being Cu and unavoidable impurities.
[0006] Furthermore, the particle size distribution of the powder is D10=15~25μm, D50=35~45μm, D90=55~65μm; the sphericity of the powder is ≥92%; the Hall flow rate is ≤18s / 50g; and the loose packing density is ≥4.6g / cm³.
[0007] Furthermore, the Y2O3 particles in the powder are uniformly distributed within the copper matrix grains and at the grain boundaries, with a particle size of 5~50nm.
[0008] In a second aspect, the present invention provides a method for preparing yttrium oxide dispersion-strengthened copper-chromium-niobium alloy powder as described in any one of the above claims, comprising the following steps: a) The raw material powder is batched according to the alloy composition, with Cr added in excess to compensate for losses in subsequent processes; b) The mixed powder obtained in step a) is subjected to high-energy ball milling; c) Perform radio frequency plasma spheroidization treatment on the composite powder obtained in step b); d) The spherical powder obtained in step c) is dried, classified, and sieved.
[0009] Furthermore, in step b), the ball-to-material ratio of the high-energy ball mill is 10:1 to 15:1, the ball milling speed is 300 to 450 rpm, the ball milling time is 20 to 40 hours, the ball milling medium is anhydrous ethanol, and the amount added is 0.5% to 1.0% of the total mass of the powder.
[0010] Furthermore, the process parameters for the radio frequency plasma spheroidization treatment in step c) are: plasma generator power 25~45kW, powder feeding rate 10~25g / min, carrier gas flow rate 3~6L / min, and working gas is argon or a mixture of argon and hydrogen.
[0011] Thirdly, the present invention provides a laser selective melting forming method for forming alloy powder according to any one of claims 1 to 3 or alloy powder prepared by any one of claims 4 to 6, comprising the following steps: (1) Preheat the substrate to 200~500°C and fill the molding chamber with a protective atmosphere so that the oxygen content is less than 100ppm; (2) The alloy powder is melted and formed layer by layer by laser. The laser power is 300~500W, the scanning speed is 600~1200mm / s, the scanning distance is 0.08~0.12mm, and the powder layer thickness is 30~50μm. (3) Post-processing of the formed parts.
[0012] Furthermore, during the laser selective melting and forming process, the volume energy density is 60~120 J / mm³.
[0013] Furthermore, the post-processing in step (3) includes at least one of stress-relief annealing, hot isostatic pressing, and aging heat treatment; The stress-relief annealing temperature is 400~600℃, and the holding time is 1~2 hours; The hot isostatic pressing treatment is performed at a temperature of 980~1050℃, a pressure of 150~200MPa, and a holding time of 2~4 hours. The aging heat treatment temperature is 450~550℃, and the holding time is 2~4 hours.
[0014] Furthermore, the alloy component has a conductivity ≥54% IACS, a room temperature tensile strength ≥904MPa, and a 400℃ tensile strength ≥471MPa.
[0015] In summary, the beneficial effects of the present invention are as follows: The present invention relates to a yttrium oxide dispersion-strengthened copper-chromium-niobium alloy and its preparation method. The specific percentage content of the copper-chromium-niobium alloy is as follows: Cr content is 3.5~4.5%, Nb content is 1.8~2.2%, Y2O3 content is 0.05~0.5%, O content (excluding oxygen combined with Y2O3) is ≤0.04%, Fe content is ≤0.05%, and the balance is Cu. The specific preparation steps are as follows: (1) ball milling and mixing; (2) plasma spheroidizing and drying the mixed powder and sieving; (3) laser selective melting and forming of the composite powder; (4) stress-relief annealing of the obtained alloy block; (5) hot isostatic pressing treatment of the annealed alloy block; (6) aging treatment of the hot isostatic pressed alloy block. This invention designs the composition of copper-chromium-niobium alloys by reducing the content of Cr and Nb elements and introducing Y2O3 to refine the microstructure. Furthermore, a three-stage heat treatment is used to eliminate alloy defects and promote the precipitation of precipitates. As a result, the copper-chromium-niobium alloy prepared by this invention not only ensures high electrical and thermal conductivity but also has a precipitation and dispersion synergistic strengthening mechanism, thereby improving the high-temperature mechanical properties of the alloy.
[0016] This invention relates to a yttrium oxide dispersion-strengthened copper-chromium-niobium alloy and its preparation method. This method fundamentally improves the processing performance of copper-chromium-niobium alloys. By combining mechanical alloying and radio frequency plasma spheroidization processes, yttrium oxide dispersion-strengthened copper-chromium-niobium alloy powder with high sphericity, good flowability, and suitability for 3D printing can be prepared. Subsequent laser selective melting and three-stage heat treatment using stress-relief annealing, hot isostatic pressing, and aging allows for comprehensive control of alloy properties through optimization of relevant process parameters, resulting in a yttrium oxide dispersion-strengthened copper-chromium-niobium alloy with high density, excellent high-temperature strength, and good thermal conductivity.
[0017] Firstly, by precisely introducing nano-sized Y2O3 ceramic particles into the copper alloy composition system, a stable second phase with uniform dispersion is formed in the copper matrix, achieving a significant dispersion strengthening effect. This also greatly improves the absorption rate of the copper alloy powder for infrared lasers commonly used in SLM (Surface Mount Laser) processes. This characteristic effectively broadens the process window for SLM forming, significantly reduces the inherent laser energy reflection loss of high-reflectivity copper-based materials, and thus reduces the risk of thermal damage to the optical path system and typical metallurgical defects such as incomplete fusion and porosity inside the formed parts.
[0018] Secondly, the copper alloy designed in this invention constructs a composite strengthening system with the synergistic effect of Cr2Nb precipitation strengthening and Y2O3 dispersion strengthening, which significantly improves the alloy's high-temperature instantaneous strength, high-temperature creep resistance, and long-term thermal stability. Test results show that the strength retention rate of this alloy at 800℃ is significantly better than that of the undoped Y2O3 GRCop-42 alloy, exhibiting superior high-temperature service potential.
[0019] Finally, this invention innovatively constructs a three-stage synergistic heat treatment process of stress-relief annealing, hot isostatic pressing, and aging treatment after additive manufacturing, effectively eliminating defects such as residual stress, microporosity, and microcracks inside SLM formed parts. While maintaining the intrinsic high thermal conductivity of the copper matrix, this process enables the formed parts to achieve room temperature / high temperature mechanical properties and density at the level of forgings, and possesses excellent airtightness, fully meeting the long-life and high-reliability service requirements of the combustion chamber and tail nozzle lining of next-generation liquid rocket engines. Attached Figure Description
[0020] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0021] Figure 1 Here is a SEM image of the copper-chromium-niobium alloy powder obtained in Example 1; Figure 2 Here is a SEM image of the copper-chromium-niobium alloy powder obtained in Example 2; Figure 3 This is a particle size distribution diagram of the copper-chromium-niobium alloy powder obtained in Example 3. Detailed Implementation
[0022] The present invention will now be described in further detail with reference to the accompanying drawings. These drawings are simplified schematic diagrams, illustrating only the basic structure of the invention, and therefore only show the components relevant to the invention.
[0023] Please see Figures 1-3In a first aspect, the present invention provides a yttrium oxide dispersion-strengthened copper-chromium-niobium alloy powder, which is composed of the following mass percentage components: Cr 3.5%~4.5%, Nb 1.8%~2.2%, Y2O3 0.05%~0.5%, with the balance being Cu and unavoidable impurities, namely: O (except for oxygen bound to Y2O3) ≤0.04%, Fe ≤0.05%, with the balance being Cu.
[0024] Furthermore, the particle size distribution of the powder is D10=15~25μm, D50=35~45μm, D90=55~65μm; the sphericity of the powder is ≥92%; the Hall flow rate is ≤18s / 50g; and the loose packing density is ≥4.6g / cm³.
[0025] Furthermore, the Y2O3 particles in the powder are uniformly distributed within the copper matrix grains and at the grain boundaries, with a particle size of 5~50nm.
[0026] In a second aspect, the present invention provides a method for preparing yttrium oxide dispersion-strengthened copper-chromium-niobium alloy powder as described in any one of the above claims, comprising the following steps: a) The raw material powder is batched according to the alloy composition, with Cr added in excess to compensate for losses in subsequent processes; b) The mixed powder obtained in step a) is subjected to high-energy ball milling; c) Perform radio frequency plasma spheroidization treatment on the composite powder obtained in step b); d) The spherical powder obtained in step c) is dried, classified, and sieved.
[0027] Furthermore, in step b), the ball-to-material ratio of the high-energy ball mill is 10:1 to 15:1, the ball milling speed is 300 to 450 rpm, the ball milling time is 20 to 40 hours, the ball milling medium is anhydrous ethanol, and the amount added is 0.5% to 1.0% of the total mass of the powder.
[0028] Furthermore, the process parameters for the radio frequency plasma spheroidization treatment in step c) are: plasma generator power 25~45kW, powder feeding rate 10~25g / min, carrier gas flow rate 3~6L / min, and working gas is argon or a mixture of argon and hydrogen.
[0029] Thirdly, the present invention provides a laser selective melting forming method for forming alloy powder according to any one of claims 1 to 3 or alloy powder prepared by any one of claims 4 to 6, comprising the following steps: (1) Preheat the substrate to 200~500°C and fill the molding chamber with a protective atmosphere so that the oxygen content is less than 100ppm; (2) The alloy powder is melted and formed layer by layer by laser. The laser power is 300~500W, the scanning speed is 600~1200mm / s, the scanning distance is 0.08~0.12mm, and the powder layer thickness is 30~50μm. (3) Post-processing of the formed parts.
[0030] Furthermore, during the laser selective melting and forming process, the volume energy density is 60~120 J / mm³.
[0031] Furthermore, the post-processing in step (3) includes at least one of stress-relief annealing, hot isostatic pressing, and aging heat treatment; The stress-relief annealing temperature is 400~600℃, and the holding time is 1~2 hours; The hot isostatic pressing treatment is performed at a temperature of 980~1050℃, a pressure of 150~200MPa, and a holding time of 2~4 hours. The aging heat treatment temperature is 450~550℃, and the holding time is 2~4 hours.
[0032] Furthermore, the alloy component has a conductivity ≥54% IACS, a room temperature tensile strength ≥904MPa, and a 400℃ tensile strength ≥471MPa.
[0033] Specifically, the following embodiments will be described in further detail: Example 1
[0034] (1) Weigh according to the alloy design composition: Cr powder accounts for 4.0% of the mass, Nb powder accounts for 2.0% of the mass, nano Y2O3 powder accounts for 0.3% of the mass, and the rest is gas atomized pure copper powder, of which Cr powder is compensated for by 0.1%.
[0035] (2) Load the prepared powder into the stainless steel grinding jar of a high-energy planetary ball mill. Select a mixture of zirconia grinding balls with diameters of 5 mm and 10 mm, and set the ball-to-powder ratio to 10:1. Add 0.8% anhydrous ethanol by weight of the total powder as the grinding medium. After evacuating the grinding jar, fill it with high-purity argon for protection. Set the grinding speed to 350 rpm and the total grinding time to 30 hours.
[0036] (3) The mechanically alloyed powder is fed into a radio frequency inductively coupled plasma system for spheroidization. The process parameters are set as follows: plasma generator power 35kW, frequency 3MHz. The working gas is argon and 3% hydrogen, and the carrier gas flow rate is 4L / min. The powder feeding rate is controlled at 15g / min.
[0037] (4) Collect the spheroidized powder and sieve it in an argon-protected glove box. Select powder with a particle size range of 15~63μm for 3D printing. The powder D50 is 38.5μm, the sphericity test result is 94%, the Hall flow rate is 15.8s / 50g, and the loose density is 4.75g / cm³.
[0038] (5) The obtained copper-chromium-niobium composite powder was printed using a laser selective melting forming equipment. The protective atmosphere was argon with an oxygen content of less than 80 ppm. The substrate was preheated to 200°C, the laser power was set to 380W, the scanning speed was 850 mm / s, the scanning spacing was 0.09 mm, and the powder layer thickness was 30 μm. A strip scanning strategy was adopted with a strip width of 5 mm and an interlayer rotation of 67°.
[0039] (6) Stress-relief annealing: After printing, place the substrate and the same parts in a vacuum annealing furnace, keep it at 475°C for 2 hours, and then cool it down to below 100°C before taking it out of the furnace.
[0040] (7) The sample is separated from the substrate by wire cutting and the surface is sandblasted to remove the unmelted powder adhering to the surface.
[0041] (8) Perform hot isostatic pressing on the printed parts. The protective atmosphere is argon, the temperature is increased to 1025℃ at a rate of 10℃ / min, the pressure is 175MPa, and the temperature and pressure are maintained for 3 hours.
[0042] (9) After hot isostatic pressing, a low-temperature aging treatment is performed: heat treatment at 475℃ for 3 hours to obtain a copper-chromium-niobium alloy component with a conductivity of 60% IACS, a room temperature tensile strength of 904MPa, and a tensile strength of 471MPa at 400℃. Example 2
[0043] (1) Weigh according to the alloy design composition: Cr powder accounts for 3.5% of the mass, Nb powder accounts for 1.75% of the mass, nano Y2O3 powder accounts for 0.1% of the mass, and the rest is gas atomized pure copper powder, of which Cr powder is compensated for by 0.1%.
[0044] (2) Load the prepared powder into the stainless steel grinding jar of the high-energy planetary ball mill. Select a mixture of zirconia grinding balls with diameters of 5 mm and 10 mm, and set the ball-to-powder ratio to 10:1. Add 0.8% anhydrous ethanol as the medium, which is the total mass of the powder. After evacuating the grinding jar, fill it with high-purity argon for protection. Set the grinding speed to 350 rpm and the total grinding time to 20 hours.
[0045] (3) The mechanically alloyed powder is fed into a radio frequency inductively coupled plasma system for spheroidization. The process parameters are set as follows: plasma generator power 35kW, frequency 3MHz. The working gas is argon and 3% hydrogen, and the carrier gas flow rate is 4L / min. The powder feeding rate is controlled at 15g / min.
[0046] (4) Collect the spheroidized powder and sieve it in an argon-protected glove box. Select powder with a particle size range of 15~63μm for 3D printing.
[0047] (5) The obtained copper-chromium-niobium composite powder was printed using a laser selective melting forming equipment. The protective atmosphere was argon with an oxygen content of less than 80 ppm. The substrate was preheated to 200°C, the laser power was set to 400W, the scanning speed was 900 mm / s, the scanning spacing was 0.09 mm, and the powder layer thickness was 30 μm. A strip scanning strategy was adopted with a strip width of 5 mm and an interlayer rotation of 67°.
[0048] (6) Stress-relief annealing: After printing, place the substrate and the same parts in a vacuum annealing furnace, keep it at 475°C for 2 hours, and then cool it down to below 100°C before taking it out of the furnace.
[0049] (7) The sample is separated from the substrate by wire cutting and the surface is sandblasted to remove the unmelted powder adhering to the surface.
[0050] (8) Perform hot isostatic pressing on the printed parts. The protective atmosphere is argon, and the temperature is raised to 980℃ at a rate of 10℃ / min. The pressure is 160MPa, and the temperature and pressure are maintained for 3 hours.
[0051] (9) After hot isostatic pressing, a low-temperature aging treatment is carried out: heat treatment at 475℃ for 3 hours, and a copper-chromium-niobium alloy part with a conductivity of 54% IACS, a room temperature tensile strength of 950MPa, and a tensile strength of 514MPa at 400℃ can be obtained. Example 3
[0052] (1) Weigh according to the alloy design composition: Cr powder accounts for 4.0% of the mass, Nb powder accounts for 2.0% of the mass, nano Y2O3 powder accounts for 0.3% of the mass, and the rest is gas atomized pure copper powder, of which Cr powder is compensated for by 0.1%.
[0053] (2) Load the prepared powder into the stainless steel grinding jar of a high-energy planetary ball mill. Select a mixture of zirconia grinding balls with diameters of 5 mm and 10 mm, and set the ball-to-powder ratio to 10:1. Add 0.8% anhydrous ethanol by weight of the total powder as the grinding medium. After evacuating the grinding jar, fill it with high-purity argon for protection. Set the grinding speed to 350 rpm and the total grinding time to 30 hours.
[0054] (3) The mechanically alloyed powder is fed into a radio frequency inductively coupled plasma system for spheroidization. The process parameters are set as follows: plasma generator power 35kW, frequency 3MHz. The working gas is argon and 3% hydrogen, and the carrier gas flow rate is 4L / min. The powder feeding rate is controlled at 15g / min.
[0055] (4) Collect the spheroidized powder and sieve it in an argon-protected glove box. Select powder with a particle size range of 15~45μm for 3D printing.
[0056] (5) The obtained copper-chromium-niobium composite powder was printed using a laser selective melting forming equipment. The protective atmosphere was argon with an oxygen content of less than 80 ppm. The substrate was preheated to 200°C, the laser power was set to 380W, the scanning speed was 850 mm / s, the scanning spacing was 0.09 mm, and the powder layer thickness was 30 μm. A strip scanning strategy was adopted with a strip width of 5 mm and an interlayer rotation of 67°.
[0057] (6) Stress-relief annealing: After printing, place the substrate and the same parts in a vacuum annealing furnace, keep it at 475°C for 2 hours, and then cool it down to below 100°C before taking it out of the furnace.
[0058] (7) The sample is separated from the substrate by wire cutting and the surface is sandblasted to remove the unmelted powder adhering to the surface.
[0059] (8) Perform hot isostatic pressing on the printed parts. The protective atmosphere is argon, the temperature is increased to 1025℃ at a rate of 10℃ / min, the pressure is 175MPa, and the temperature and pressure are maintained for 3 hours.
[0060] (9) After hot isostatic pressing, a low-temperature aging treatment is performed: heat treatment at 475℃ for 3 hours to obtain a copper-chromium-niobium alloy component with a conductivity of 63% IACS, a room temperature tensile strength of 911MPa, and a tensile strength of 493MPa at 400℃.
[0061] Comparative Example 1: This comparative example uses commercially available GRCop-42 powder without yttrium oxide doping for printing.
[0062] (1) The atomized powder was sieved in an argon-protected glove box, and powder with a particle size of 15~63μm was selected for 3D printing.
[0063] (2) GRCop-42 powder was printed using a laser selective melting forming equipment. The protective atmosphere was argon with an oxygen content of less than 80 ppm. The substrate was preheated to 200°C, the laser power was set to 380W, the scanning speed was 850 mm / s, the scanning spacing was 0.09 mm, and the powder layer thickness was 30 μm. A strip scanning strategy was adopted with a strip width of 5 mm and an interlayer rotation of 67°.
[0064] (3) Stress relief annealing: After printing, the substrate and the same parts are placed in a vacuum annealing furnace and kept at 475°C for 2 hours. Then, the substrate is cooled to below 100°C and taken out of the furnace.
[0065] (4) The sample is separated from the substrate by wire cutting and the surface is sandblasted to remove the unmelted powder adhering to the surface.
[0066] (5) Perform hot isostatic pressing on the printed parts. The protective atmosphere is argon, and the temperature is increased to 1025℃ at a rate of 10℃ / min, the pressure is 175MPa, and the temperature and pressure are maintained for 3 hours.
[0067] (6) After hot isostatic pressing, a low-temperature aging treatment is performed: holding at 475℃ for 3 hours. The resulting alloy has a room temperature tensile strength of 730MPa and a conductivity of 65%IACS. At 400℃, the tensile strength is only 238MPa. The high-temperature strength is too low and cannot meet the requirements of key hot-end components for spacecraft.
[0068] Comparative Example 2 uses the powder and printing process of Example 1, but does not perform hot isostatic pressing or aging treatment, only stress-relieving annealing.
[0069] (1) Weigh according to the alloy design composition: Cr powder accounts for 4.0% of the mass, Nb powder accounts for 2.0% of the mass, nano Y2O3 powder accounts for 0.3% of the mass, and the rest is gas atomized pure copper powder, of which Cr powder is compensated for by 0.1%.
[0070] (2) Load the prepared powder into the stainless steel grinding jar of a high-energy planetary ball mill. Select a mixture of zirconia grinding balls with diameters of 5 mm and 10 mm, and set the ball-to-powder ratio to 10:1. Add 0.8% anhydrous ethanol by weight of the total powder as the grinding medium. After evacuating the grinding jar, fill it with high-purity argon for protection. Set the grinding speed to 350 rpm and the total grinding time to 30 hours.
[0071] (3) The mechanically alloyed powder is fed into a radio frequency inductively coupled plasma system for spheroidization. The process parameters are set as follows: plasma generator power 35kW, frequency 3MHz. The working gas is argon and 3% hydrogen, and the carrier gas flow rate is 4L / min. The powder feeding rate is controlled at 15g / min.
[0072] (4) Collect the spheroidized powder and sieve it in an argon-protected glove box. Select powder with a particle size range of 15~63μm for 3D printing. The powder D50 is 38.5μm, the sphericity test result is 94%, the Hall flow rate is 15.8s / 50g, and the loose density is 4.75g / cm³.
[0073] (5) The obtained copper-chromium-niobium composite powder was printed using a laser selective melting forming equipment. The protective atmosphere was argon with an oxygen content of less than 80 ppm. The substrate was preheated to 200°C, the laser power was set to 380W, the scanning speed was 850 mm / s, the scanning spacing was 0.09 mm, and the powder layer thickness was 30 μm. A strip scanning strategy was adopted with a strip width of 5 mm and an interlayer rotation of 67°.
[0074] (6) Stress-relief annealing: After printing, place the substrate and the same parts in a vacuum annealing furnace, keep it at 475°C for 2 hours, and then cool it down to below 100°C before taking it out of the furnace.
[0075] (7) The sample was separated from the substrate by wire cutting and the surface was sandblasted to remove the unmelted powder adhering to the surface. The obtained alloy has a room temperature tensile strength of only 563 MPa, a conductivity of 24% IACS, and a tensile strength of only 271 MPa at 400℃. The high temperature strength is too low to meet the requirements of key hot-end components for spacecraft.
[0076] The copper-chromium-niobium alloys obtained in the above embodiments and comparative examples are listed in Table 1: Table 1 Comparison of Examples and Comparative Examples Example 1 The microstructure is uniform, and the tensile strength at room temperature is 904 MPa, while the tensile strength at 400℃ is 471 MPa. Example 2 The microstructure is uniform, and the tensile strength at room temperature is 950 MPa, while the tensile strength at 400℃ is 514 MPa. Example 3 The microstructure is uniform, the room temperature tensile strength is 911 MPa, and the 400℃ tensile strength is 493 MPa. Comparative Example 1 The precipitate phase is large in size and difficult to disperse. Comparative Example 2 The alloy exhibits incomplete fusion defects and severe segregation inclusions. The present invention relates to a yttrium oxide dispersion-strengthened copper-chromium-niobium alloy and its preparation method. The specific percentage content of the copper-chromium-niobium alloy is as follows: Cr content is 3.5~4.5%, Nb content is 1.8~2.2%, Y2O3 content is 0.05~0.5%, O content (excluding oxygen combined with Y2O3) is ≤0.04%, Fe content is ≤0.05%, and the balance is Cu. The specific preparation steps are as follows: (1) ball milling and mixing; (2) plasma spheroidizing and drying the mixed powder and sieving; (3) laser selective melting and forming of the composite powder; (4) stress-relief annealing of the obtained alloy block; (5) hot isostatic pressing treatment of the annealed alloy block; (6) aging treatment of the hot isostatic pressed alloy block. This invention designs the composition of copper-chromium-niobium alloys by reducing the content of Cr and Nb elements and introducing Y2O3 to refine the microstructure. Furthermore, a three-stage heat treatment is used to eliminate alloy defects and promote the precipitation of precipitates. As a result, the copper-chromium-niobium alloy prepared by this invention not only ensures high electrical and thermal conductivity but also has a precipitation and dispersion synergistic strengthening mechanism, thereby improving the high-temperature mechanical properties of the alloy.
[0077] This invention relates to a yttrium oxide dispersion-strengthened copper-chromium-niobium alloy and its preparation method. This method fundamentally improves the processing performance of copper-chromium-niobium alloys. By combining mechanical alloying and radio frequency plasma spheroidization processes, yttrium oxide dispersion-strengthened copper-chromium-niobium alloy powder with high sphericity, good flowability, and suitability for 3D printing can be prepared. Subsequent laser selective melting and three-stage heat treatment using stress-relief annealing, hot isostatic pressing, and aging allows for comprehensive control of alloy properties through optimization of relevant process parameters, resulting in a yttrium oxide dispersion-strengthened copper-chromium-niobium alloy with high density, excellent high-temperature strength, and good thermal conductivity.
[0078] Firstly, by precisely introducing nano-sized Y2O3 ceramic particles into the copper alloy composition system, a stable second phase with uniform dispersion is formed in the copper matrix, achieving a significant dispersion strengthening effect. This also greatly improves the absorption rate of the copper alloy powder for infrared lasers commonly used in SLM (Surface Mount Laser) processes. This characteristic effectively broadens the process window for SLM forming, significantly reduces the inherent laser energy reflection loss of high-reflectivity copper-based materials, and thus reduces the risk of thermal damage to the optical path system and typical metallurgical defects such as incomplete fusion and porosity inside the formed parts.
[0079] Secondly, the copper alloy designed in this invention constructs a composite strengthening system with the synergistic effect of Cr2Nb precipitation strengthening and Y2O3 dispersion strengthening, which significantly improves the alloy's high-temperature instantaneous strength, high-temperature creep resistance, and long-term thermal stability. Test results show that the strength retention rate of this alloy at 800℃ is significantly better than that of the undoped Y2O3 GRCop-42 alloy, exhibiting superior high-temperature service potential.
[0080] Finally, this invention innovatively constructs a three-stage synergistic heat treatment process of stress-relief annealing, hot isostatic pressing, and aging treatment after additive manufacturing, effectively eliminating defects such as residual stress, microporosity, and microcracks inside SLM formed parts. While maintaining the intrinsic high thermal conductivity of the copper matrix, this process enables the formed parts to achieve room temperature / high temperature mechanical properties and density at the level of forgings, and possesses excellent airtightness, fully meeting the long-life and high-reliability service requirements of the combustion chamber and tail nozzle lining of next-generation liquid rocket engines.
[0081] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any other way. Any person skilled in the art may make changes or equivalent variations to the disclosed technical content and apply them to other fields. However, any simple modifications, equivalent variations, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention. For those skilled in the art, the specific meaning of the above terms in the present invention can be understood through specific circumstances.
Claims
1. A yttrium oxide dispersion-strengthened copper-chromium-niobium alloy powder, characterized in that, It consists of the following components by mass percentage: Cr 3.5%~4.5%, Nb 1.8%~2.2%, Y2O3 0.05%~0.5%, with the balance being Cu and unavoidable impurities.
2. The yttrium oxide dispersion-strengthened copper-chromium-niobium alloy powder according to claim 1, characterized in that: The powder has a particle size distribution of D10=15~25μm, D50=35~45μm, and D90=55~65μm; powder sphericity ≥92%; Hall flow rate ≤18s / 50g; and loose packing density ≥4.6g / cm³.
3. The yttrium oxide dispersion-strengthened copper-chromium-niobium alloy powder according to claim 1, characterized in that: The Y2O3 particles in the powder are uniformly distributed inside the copper matrix grains and at the grain boundaries, with a particle size of 5~50nm.
4. A method for preparing yttrium oxide dispersion-strengthened copper-chromium-niobium alloy powder according to any one of claims 1 to 3, characterized in that, Includes the following steps: a) The raw material powder is batched according to the alloy composition, with Cr added in excess to compensate for losses in subsequent processes; b) The mixed powder obtained in step a) is subjected to high-energy ball milling; c) Perform radio frequency plasma spheroidization treatment on the composite powder obtained in step b); d) The spherical powder obtained in step c) is dried, classified, and sieved.
5. The method according to claim 4, characterized in that: In step b), the ball-to-material ratio of the high-energy ball mill is 10:1 to 15:1, the ball milling speed is 300 to 450 rpm, the ball milling time is 20 to 40 hours, the ball milling medium is anhydrous ethanol, and the amount added is 0.5% to 1.0% of the total mass of the powder.
6. The method according to claim 4, characterized in that: The process parameters for the radio frequency plasma spheroidization treatment in step c) are: plasma generator power 25~45kW, powder feeding rate 10~25g / min, carrier gas flow rate 3~6L / min, and working gas is argon or a mixture of argon and hydrogen.
7. A laser selective melting forming method for forming alloy powder according to any one of claims 1 to 3 or alloy powder prepared by any one of claims 4 to 6, characterized in that, Includes the following steps: (1) Preheat the substrate to 200~500°C and fill the molding chamber with a protective atmosphere so that the oxygen content is less than 100ppm; (2) The alloy powder is melted and formed layer by layer by laser. The laser power is 300~500W, the scanning speed is 600~1200mm / s, the scanning distance is 0.08~0.12mm, and the powder layer thickness is 30~50μm. (3) Post-processing of the formed parts.
8. The laser selective melting forming method according to claim 7, characterized in that: During the laser selective melting and forming process, the volume energy density is 60~120J / mm³.
9. The laser selective melting forming method according to claim 7, characterized in that: The post-processing in step (3) includes at least one of stress-relief annealing, hot isostatic pressing, and aging heat treatment; The stress-relief annealing temperature is 400~600℃, and the holding time is 1~2 hours; The hot isostatic pressing treatment is performed at a temperature of 980~1050℃, a pressure of 150~200MPa, and a holding time of 2~4 hours. The aging heat treatment temperature is 450~550℃, and the holding time is 2~4 hours.
10. A copper-chromium-niobium alloy component prepared by the method according to any one of claims 7 to 9, characterized in that: The alloy component has a conductivity ≥54% IACS, a room temperature tensile strength ≥904MPa, and a 400℃ tensile strength ≥471MPa.